2003
DOI: 10.1038/sj.bjp.0705232
|View full text |Cite
|
Sign up to set email alerts
|

PPAR‐α and ‐γ but not ‐δ agonists inhibit airway inflammation in a murine model of asthma: in vitro evidence for an NF‐κB‐independent effect

Abstract: 1 Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that have been proposed to regulate inflammation by antagonising the nuclear factor-kB (NF-kB) signalling pathway. We investigated the role of PPARs using synthetic agonists in murine models of airway inflammation, and addressed the possible effect on NF-kB signalling in vitro using a human epithelial cell line, A549. 2 Sensitised BALB/c mice exposed to an aerosol solution of ovalbumin had an increased number of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
3
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 36 publications
6
106
3
2
Order By: Relevance
“…Other authors suggest the SUMOylation of the PPAR␥ ligand-binding domain, which mediates transrepression of inflammatory response genes by PPAR␥ ligands (Pascual et al, 2005). By contrast, Trifilieff et al (2003) have shown that although PPAR␥ ligands are able to reduce inflammation, this effect might not be mediated by antagonism of the NF-B pathway. In the present study, we demonstrate that MPs from human T cells exert their effects on NF-B cascade at mRNA and protein expressions.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Other authors suggest the SUMOylation of the PPAR␥ ligand-binding domain, which mediates transrepression of inflammatory response genes by PPAR␥ ligands (Pascual et al, 2005). By contrast, Trifilieff et al (2003) have shown that although PPAR␥ ligands are able to reduce inflammation, this effect might not be mediated by antagonism of the NF-B pathway. In the present study, we demonstrate that MPs from human T cells exert their effects on NF-B cascade at mRNA and protein expressions.…”
Section: Downloaded Frommentioning
confidence: 99%
“…These TF are involved in cholesterol (LXR), triglycerides (PPAR), bile acids (VDR, farnesoid X-activated receptor, LXR), steroids (CAR, PXR), and bilirubin (CAR, PXR) (Handschin and Meyer, 2005) metabolism. TF also interact with many other cardiovascular-related pathways, including the cytokines for PPAR (Jones et al, 2002;Trifilieff et al, 2003). To conclude, a biological system approach could be defined for better understanding on the relation of each TF with every P450 or other constituent candidate marker measured in PBMC.…”
Section: Downloaded Frommentioning
confidence: 99%
“…37,86,87 These effects are likely mediated by modulating the function of multiple cell types, including macrophages, T cells, eosinophils, mast cells, epithelial cells, and smooth muscle cells. In vivo, nebulization of PPARa and PPARg ligands decreases allergen-induced eosinophilia and mucus production, as well as cytokine production (IL-2, IL-4, IL-5, IL-6, and IL-13), serum IgE and IgG1, TGF-b, and the expression of GATA-3, a transcription factor that promotes a Th2-type response in T cells.…”
Section: Asthmamentioning
confidence: 99%